Compliance Assessment of ISO 21001:2018 Clause 8.5 in the Systems Engineering Program of Universidad Autónoma del Perú - Costa Faura, Marcel (2020)
The Universidad Autónoma del Perú (UA) implemented its Quality Management System in 2015 achieving the ISO 9001: 2015 certification in February 2019. This certification covers all the processes related to student support services, laboratories, degrees and diplomas among others. Due the specificity for educational organizations of ISO 21001: 2018 standard, the UA considered to align the current management system with the ISO 21001: 2018 requirements, beginning with the Systems Engineering Program. This paper displays the methodology and the results of the compliance assessment of the existing processes against the ISO 21001: 2018 Clause 8.5 in February 2019. As a result, it was found that the current management system meets the common requirements between ISO 9001:2015 and ISO 21001:2018. Nevertheless, there are some breaches in Clauses 8.5.1, 8.5. 2, 8.5.3, 8.5.5 and 8.5.6. Finally, the corresponding gaps were identified and the respective continuous improvement plans were developed.